Revisiting the formation mechanism of diarylamines via Smiles rearrangement. (12th September 2022) - Murillo, Fernando; Quintal, Alan; Dzib, Eugenia; Zarate, Ximena; Fernández‐Herrera, María A.; Merino, Gabriel
Abstract: The mechanisms proposed for the synthesis of diarylamines from diarylsulfinamides are revisited via quantum chemical computations, verifying the 3‐ exo ‐trig Smiles rearrangement as the most viable pathway. Diarylamine precursors with sterically hindered, electron‐rich, or electron‐deficient N ‐aryl rings do not alter the barriers. However, the effects of the substituent on the S ‐aryl ring of monosubstituted, dimonosubstituted, and trisubstituted diarylsulfinamides can drastically change the rearrangement barriers. Furthermore, our results of rate constants computed at different temperatures show that the temperature rise favors the 3‐ exo ‐trig Smiles rearrangement reactions. Abstract : The most viable pathway for the formation of diarylamines from diarylsulfinamides is the 3‐ exo ‐trig Smiles rearrangement. Substituents on the N ‐aryl ring of diarylamine precursors do not alter the barriers, while those on the S ‐aryl ring can change them drastically.